Outside the fold : conversion, modernity, and belief - Viswanathan, Gauri (ACLS Humanities E-Book., 1998)
"Outside the Fold is a radical reexamination of religious conversion. Gauri Viswanathan skillfully argues that conversion is an interpretive act that belongs in the realm of cultural criticism. To that end, this work examines key moments in colonial and postcolonial history to show how conversion questions the limitations of secular ideologies, particularly the discourse of rights central to both the British empire and the British nation-state. Implicit in such questioning is an attempt to construct an alternative epistemological and ethical foundation of national community. Viswanathan grounds her study in an examination of two simultaneous and, she asserts, linked events: the legal emancipation of religious minorities in England and the acculturation of colonial subjects to British rule. The author views these two apparently disparate events as part of a common pattern of national consolidation that produced the English state. She seeks to explain why resistance, in both cases, frequently took the form of religious conversion, especially to "minority" or alternative religions. Confronting the general characterization of conversion as assimilative and annihilating of identity, Viswanathan demonstrates that a willful change of religion can be seen instead as an act of opposition. Outside the Fold concludes that, as a form of cultural crossing, conversion comes to represent a vital release into difference."